The Effect of Pregnancy Dance on Maternal Mental Health from Pregnancy to the Postpartum Period - Wiwit Vitania; Yustika Rahmawati Pratami; Hasnia Hasnia; Bq Safinatunnaja; Nurul Hidayati; Fenska Narly Makualaina (Indonesian Journal of Global Health Research, 2026)
Maternal mental health from pregnancy to the postpartum period represents a major public health concern with substantial implications for maternal well-being and early child development. Physiological and psychological changes during pregnancy increase vulnerability to anxiety, stress, and depression, particularly in settings with limited access to mental health services. Pregnancy dance has emerged as a non-pharmacological, mind–body intervention that may support maternal psychological well-being. Objective to examine the effect of pregnancy dance on maternal mental health from pregnancy through the postpartum period. A quasi-experimental pretest–posttest design was applied. The study involved 32 pregnant women in the second and third trimesters who participated in a structured pregnancy dance programme conducted 2–3 times per week during pregnancy. The sampling technique used was purposive sampling. Mental health outcomes were assessed using the Edinburgh Postnatal Depression Scale and the Depression Anxiety Stress Scale (DASS-21) at three time points: before the intervention, after the antenatal intervention, and during the postpartum period. Statistical analyses were performed according to data distribution, with a significance level of α = 0.05. Significant reductions in depression, anxiety, and stress scores were observed following the pregnancy dance intervention (p < 0.001). Improvements in mental health were sustained into the postpartum period, with most participants classified as having a low risk of mental health disorders. The greatest reduction was observed in stress scores, followed by anxiety and depression. Pregnancy dance is an effective intervention for improving maternal mental health from pregnancy to the postpartum period. This approach offers a safe, low-cost, and feasible promotive and preventive strategy for integration into comprehensive antenatal care, particularly in areas with limited access to mental health services.